Suara Perempuan yang Terbungkam: Reinterpretasi Teks Markus 7:24-30 - Randan, Sindy (JURNAL TERUNA BHAKTI, 2022)
This article aims to analyze the narrative of Mark 7:24-30 from a feminist perspective. The patriarchal interpretation of Mark 7:24-30 places the Syro-Phoenician Woman, which implicitly reflects the form of judging women with their identity as Canaanite women. The action of Jesus, marked by rejection, seems to represent the patriarchy rather than his side with the woman. This article proposes a rereading of the narrative of Syro-Phoenician Women in Mark 7:24-30 as an attempt by Syro-Phoenician Women. The voice of the Syro Phoenician Woman indicated that the mute had spoken. His identity as a descendant of Canaan can be seen as his courage in breaking the patriarchal system. Through a study of the narrative of Mark 7:24-30 using a feminist perspective, the author can reflect on women as victims of gender inequality practices that the patriarchal system has long silenced. This study resulted in a new perspective that sided with women and the church's position in responding to the existence of women as victims of the practice of gender inequality. AbstrakArtikel ini bertujuan untuk menganalisis narasi Markus 7:24-30 dengan perspektif feminis. Penafsiran patriakrki dari Markus 7:24-30 menempatkan Perempuan Siro-Fenisia yang secara implisit mencerminkan bentuk penilaian terhadap perempuan dengan identitasnya sebagai perempuan Kanaan. Tindakan Yesus yang ditandai dengan penolakan seolah-olah mewakili kaum patriarki daripada keberpihakan-Nya kepada perempuan tersebut. Artikel ini mengusulkan pembacaan ulang narasi terhadap Perempuan Siro-Fenisia dalam Markus 7:24-30 sebagai sebuah upaya yang dilakukan oleh Perempuan Siro-Fenisia. Suara dari Perempuan Siro Fenisia menunjukkan bahwa ia yang bisu telah berbicara. Identitasnya sebagai keturunan Kanaan dapat dilihat sebagai keberaniannya dalam mendobrak sistem patriarki. Melalui kajian terhadap narasi Markus 7:24-30 dengan menggunakan perspektif feminis, penulis dapat merefleksikan perempuan sebagai korban praktik ketidaksetaraan gender yang telah lama dibungkam sistem patriarki. Kajian ini menghasilkan perspektif baru yang berpihak pada perempuan dan posisi gereja dalam menyikapi keberadaan perempuan sebagai korban praktik ketidaksetaraan gender.